Neuroepidemiology in tropical health - Preuz, Pierre-Marie; Dumas, Michel, 1934- (Academic Press, 2018)
"Neuroepidemiology in Tropical Health covers major neurological diseases of relevance in tropical settings and examines the specificities of epidemiology of neurological diseases in the context of tropical countries that face many challenges when compared to the developed world. Part One focuses on methods and their eventual specificities, and how such methods, like sampling, can be adapted for specific scenarios. Parts Two and Three discuss environmental factors and their consequences for neurology in the tropical world, as well as large geographical areas and their specificities. Finally, Part Four presents relevant neurological diseases in in-depth chapters. This invaluable information will help readers recognize the various neurological conditions presented, with the inclusion of their aetiologies and treatment in tropical areas. The book therefore fills a gap in the neuroepidemiology literature, with chapters written by an international collection of experienced authors in the field. Highlights differences and similarities between neuroepidemiology in tropical areas and temperate zones with a focus on methods and underlying factorsCovers environmental factors in the tropical world and their consequences for neurologyChapters include references (key articles, books, protocols) for additional detailed studyIncludes wide topics of neurological disease in the tropics, not only infectious diseases, but also nutrition and public health"--